Maturity, Indebtedness, and Default Risk - Chatterjee, Satyajit; Eyigungor, Burcu (American Economic Review, 2012)
We advance quantitative-theoretic models of sovereign debt by proving the existence of a downward sloping equilibrium price function for long-term debt and implementing a novel method to accurately compute it. We show that incorporating long-term debt allows the model to match Argentina's average external debt-to-output ratio, average spread on external debt, the standard deviation of spreads, and simultaneously improve upon the model's ability to account for Argentina's other cyclical facts. We also investigated the welfare properties of maturity length and showed that if the possibility of self-fulfilling rollover crises is taken into account, long-term debt is superior to short-term debt. (JEL E23, E32, F34, O11, O19)